2019
DOI: 10.1111/bph.14800
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide signalling in the brain and its control of bodily functions

Abstract: Funding information Agence Nationale de la Recherche, Grant/ Award Number: ANR-17-CE16-0015-01; Fédération Hospital-Universitaire "1000 days for health"; European Genomic Institute for Diabetes; LabEx DISTALZ Nitric oxide (NO) is a versatile molecule that plays key roles in the development and survival of mammalian species by endowing brain neuronal networks with the ability to make continual adjustments to function in response to moment-to-moment changes in physiological input. Here, we summarize the progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 287 publications
(429 reference statements)
0
47
0
4
Order By: Relevance
“…Activation of the NMDA glutamatergic receptor in postsynaptic neurons results in NO formation through a Ca +2 -dependent mechanism and activation of the nNOS (Chachlaki and Prevot, 2019; Garthwaite, 2008, 2019). Accordingly, we recently reported that the facilitatory influence of the NMDA receptor within the BNST in stress-evoked cardiovascular responses is mediated by local nNOS activation (Barretto-de-Souza et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of the NMDA glutamatergic receptor in postsynaptic neurons results in NO formation through a Ca +2 -dependent mechanism and activation of the nNOS (Chachlaki and Prevot, 2019; Garthwaite, 2008, 2019). Accordingly, we recently reported that the facilitatory influence of the NMDA receptor within the BNST in stress-evoked cardiovascular responses is mediated by local nNOS activation (Barretto-de-Souza et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the NMDA glutamate receptor is the best characterized mechanism for activation of the neuronal isoform of the neuronal nitric oxide synthase (nNOS) enzyme in the brain (Chachlaki and Prevot, 2019; Garthwaite, 2008, 2019). Accordingly, a recent study identified that control of cardiovascular responses to restraint stress by NMDA receptor in the BNST is mediated by activation of local nNOS (Barretto-de-Souza et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…71 Hence, alterations in the aquaporin system might be responsible for long-lasting or permanent adaptations of ventricular volumes after zero-gravity space flights and might be involved in many CSF disorders in which CSF dynamics are altered. A related pathway has been described for nitric oxide (NO), 72 which is delivered by neuronal or endothelial isozymes and is able to cross membranes 73,74 and AQP4 channels. It facilitates the motility and beating frequency of several ciliated epithelial cells.…”
Section: Space Flight Diseasementioning
confidence: 99%
“…All three NOSs are expressed in brain, but nNOS is the major source of NO in the nervous system. Additionally, nNOS is expressed throughout the brain during development, but the precise patterns and locations depend on the developmental stage, species, sex, brain region, and cell type of the organism (reviewed in Chachlaki & Prevot, 2020; Park et al., 2000). For example, nNOS is present in murine paraventricular nucleus (PVN) at early embryonic stages, indicating that it may be involved in the development of the PVN (McClellan et al., 2010).…”
Section: Nnos In the Developing Nervous Systemmentioning
confidence: 99%